One-Stage Nasal Soft Tissue Reconstruction with Local Flaps - Helml, Gudrun; Gregory, Henning Freiherr von; Amr, Amro; Fischer, Helmut; Gubisch, Wolfgang (Facial Plastic Surgery, 2014)
Because of better public education and earlier diagnosis of skin tumors, the number of soft tissue defects of the nose with limited size and depth after tumor resection is increasing. A variety of surgical methods such as skin grafts, regional flaps such as forehead flap, and local flaps have been described. The method of choice is dependent on the defect size, localization, skin structure and the wishes and expectations, and general condition of the patient. Nasal reconstruction for soft tissue defects in the supratip area, dorsum, and sidewalls using local rotation and/or advancement flaps is our primary option. But achieving supreme results with these non-subunit–based techniques is still a challenge. Showing schematic figures and case studies, this article is aimed at assisting surgeons in the planning and decision making of which flap is appropriate for the reconstruction of soft tissue defects of the nose.
Keywords: nasal reconstruction; soft tissue defects of the nose; local rotation flap; local advancement flap